Governance Practices in Nepalese Commercial Banks - Neupane, Shova (Nepalese Journal of Development and Rural Studies, 2020)
This article tries to to analyze the existing practices of corporate governance in commercial banks of Nepal. The state of corporate governance can have an important effect on all firms, and good corporate governance of financial firms is essential in fostering financial stability and healthy economic growth. This study found that good corporate governance frameworks help firms and countries improve accountability, more efficiently use capital, and attract quality and long-term investors at lower costs. These, in turn, contribute to a country’s competitiveness and thereby its development.The descriptive research design has been adopted for fact-finding and searching adequate information about effect of corporate governance on financial performance. In conclusion, the rapid globalization, international legal deregulation and rapid development in information technology has resulted both opportunity and challenges for the companies. In this context, the success of the organization in global arena is essentially determined by the level of corporate governance that the company is practicing. The efficient and effective corporate governance provides a competitive edge to the company. Management of commercial banks should follow the principles of sound corporate governance to ensure transparency, and accountability through their daily operational process and procedures with clients, and subsequently improve the performance, and enhance investors, shareholders, and stakeholders trust, which contribute to attain the banks goals. Banks require good corporate governance practices.